EVALUASI UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 79 TAHUN 2013 TENTANG JARINGAN DAN ANGKUTAN JALAN (STUDI KASUS TERMINAL BUSLABUAN PANDEGLANG) - Yulianti, Rachmi (Universitas Serang Raya, 2016)
Inter-regional movement of public transport in the city and between districts or cities in the province is expected to realize at least improve the quality and quantity of good infrastructure. With consideration of the author wanted to do Feasibility Evaluation Bus Terminal Labuan. The method used is descriptive qualitative. Data was collected through interviews with a number of informants that are considered relevant to the research. In this study the authors take the theory of William N Dunn, in which to evaluate a policy, there are six elements of evaluation criteria used are effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. Overall this study to describe the conclusion that the feasibility of the bus terminal Labuan who moved from village to village MargasanaTarogong Labuan Labuan has decent performances, but it's just that its facilities and infrastructure are not worth dikrnakan lack of good management of the terminal. This conclusion is based on observations and information from several informants who becomes the object of research.